A new sisorid catfish of the genus Pseudolaguvia (Teleostei: Sisoridae) from Nagaland, north-eastern India - Praveenraj, Jayasimhan; Vijayakrishnan, Balaji; Lima, Akum; Gurumayum, Shantabala Devi (Zootaxa, 2021)
Pseudolaguvia vespa, new species, is described from the Tsücha River, Mokokchung district, Nagaland, India. The new species can be distinguished from congeners in having the following combination of characters: length of dorsal-fin spine 12.3–16.8% SL, a smooth anterior edge of the dorsal-fin spine, caudal peduncle depth 9.0–10.5% SL, body depth at anus 15.6–17.7% SL, caudal fin length 20.7–24.5% SL, pectoral fin length 20.1–24.1% SL, interorbital distance 22.7–28.1% SL, thoracic adhesive apparatus extending to midway between base of last pectoral-fin ray and pelvic-fin origin, and live specimens with two irregular, chrome-yellow bands on the body.